Hypersemiotics in Printed Commercial Advertising - Moh. Masrukhi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2019)
Commercial advertising is currently created with an imaginative look. The elements are framed in verbal and nonverbal ways, and there is a structure of discourse where the message is hidden by the advertiser or copywriter. This article attempts to explore how advertisements uses verbal and nonverbal elements or signs, the relationships between these elements, and how these elements are interpreted. To understand the meaning and message of the advertisement, the elements will be analyzed with van Dijk’s concepts such as macrostructures (comprehension for complex information), superstructures (the schematic form that organizes the global meaning of a text), and microstructures (text grammars), and to understand signs especially nonverbal sign the hyper-semiotics theory will be used.